Non-Pharmacological Interventions for Anemia Treatment: Systematic Review - Sitti Zakiyyah Putri; Budu Budu; Gemini Gemini; Rosdiana Natsir (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The global prevalence of anemia in non-pregnant women, of childbearing age, is estimated at 29.0% and is more common in low- and middle-income countries, women belonging to low socioeconomic strata. iron deficiency can cause direct or risky disability. To determine the effectiveness of Non-Pharmacological Interventions for the treatment of anemia. The method used is with the help of electronic databases from journals that have been published through PubMed, Proquest, EBSCOhost, and Science Direct as many as 6 articles were reviewed from 1186 articles. The 6 articles reviewed in this study with varied respondents using patients, male rats, nurses, Sprague-Dawley (SD) Rattus norvegicus Domestica, bovine serum, premature neonates. Non-pharmacological interventions developed in the treatment of anemia in both human and animal samples as well as the development of treatment and laboratory examinations in the treatment of anemia are Nursing Delirium Screening scale, Hepcidin expression, pain identification, HM10760A, Divalent metal transporter DMT1/SLC11A2, conservative management.